ACQUISITION OF DEFINITENESS AND INDEFINITENESS BY BEHDINI KURDISH LEARNERS OF ENGLISH - TOMA, SHIVAN SHLAYMOON; HUSSEIN, KHALIDA JUMAA (Journal of Duhok University, 2020)
ABSTRACTThe acquisition of English grammatical articles by non-native speakers of English language has been the main concern of a wide range of research, especially in languages whose grammatical article system functions differently from the English grammatical article system. Behdini is a variety whose grammatical article system is different from that English grammatical parameter. Thus, the acquisition of L2 English articles among L1 Behdini speakers is investigated in this study along proposals based on the Interpretability Hypothesis (Hawkins & Hattori, 2006; Tsimpli & Dimitrakopoulou, 2007; Hawkins & Casillas, 2008), and the Full Transfer Full Access (FT/FA) hypothesis (Schwartz and Sprouse, 1994, 1996).The researcher developed a Judgement Elicitation Task (JET)   based on the following research question:Will Behdini learners’ English language proficiency level play a role in participants’ judgements? Will these learners be able to acquire English definite, indefinite, and zero articles systematically? In other words, is any development expected in Behdini learners’ acquisition of English articles? 40 Behdini L2 English learners took part in the Judgement Elicitation Task . English learners took an English language proficiency test based on which they were roughly grouped into three sub-groups: elementary (11 participants), intermediate (22 participants), and advanced (7 participants). All participants took two tests: an acceptability judgment test including 46  items (34 pure test items + 12 filler gaps) and a proficiency test with 40  items.The results of the study show that there is a transfer from L1 into the L2ers’ English interlanguage due to the finding that most participants, disregarding their proficiency level, failed to reject the ungrammatical sentences in almost all the categories. The study finds support for the FT/FA proposal, where first language transfer, second language input and access to universal grammar features are argued to have impacts on Learners of English article acquisition among L1 Behdini learners. The result  also show that learners of  English  fluctuate in their choice of articles, which is interpreted by the predictions made by the Fluctuation Theory. Uninterpretable features also, proved to be difficult to acquire by Behdini learners, a point that  can be interpreted the base form of the Interpretability Hypothesis.